Leader Reinforcement Behaviors And Employee Work Outcomes : The Mediating Role Of Leader-Member Exchange - Tng Chee, Chow (2006)
Leadership is one of the most widely studied topics in the management literature. Contemporary researches preferred transformational leadership over transactional leadership with the belief that it is the dominant model of effective leadership when dealing with employees for desired outcomes.